Hubungan Health Anxiety dengan Kualitas Hidup pada Pasien dengan Gangguan Kardiovaskuler di SMC RS Telogorejo Semarang - Noor Afiyatul Khasanah; Ni Made Ayu Wulansari; Nanang Khosim Azhari (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Cardiovascular disease (CVD) is the leading cause of death globally and can significantly impact an individual's health anxiety and quality of life. This study aimed to analyze the correlation between health anxiety and quality of life among cardiovascular patients at SMC Telogorejo hospital, Semarang. An observational analytic approach with a cross-sectional design was employed, involving 50 respondents selected through purposive sampling. Data on demographic characteristics, including age, gender, and educational background, were collected alongside assessments of health anxiety and quality of life. The majority of participants were aged 61-70 years (40.0%), predominantly male (62.0%), and had a bachelor's degree (50.0%). The findings indicated that 60.0% of respondents experienced moderate health anxiety, while 74.0% reported a moderate quality of life. Statistical analysis revealed a significant negative correlation between health anxiety and quality of life (r = -0.832, p < 0.05), suggesting that higher health anxiety is associated with a lower quality of life. The study highlights the need for addressing health anxiety to improve the well-being of cardiovascular patients. Further research is recommended to explore interventions and additional factors related to health anxiety and quality of life in cardiovascular patients across various healthcare settings.